Effect of Learning Climate and Work Overload on Adaptive Performance with Mediation of Employee Engagement among Generation Z Employees in East Java - Diva Febriani; Emma Yulianti (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines the effect of learning climate and work overload on adaptive performance, with employee engagement as a mediating variable among Generation Z employees in East Java. Methodology: A quantitative research design was employed using a survey method. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: The results indicate that learning climate has a positive and significant effect on employee engagement, while work overload has a negative and significant effect on employee engagement. Furthermore, employee engagement positively influences adaptive performance and fully mediates the relationship between learning climate and adaptive performance, as well as between work overload and adaptive performance. Findings: These findings highlight the critical role of employee engagement in translating organizational conditions into adaptive work behavior among Generation Z employees. Novelty & Originality: The novelty of this study lies in its focus on Generation Z employees in East Java, a demographic cohort that has received limited empirical attention in adaptive performance research. Its originality emerges from the simultaneous examination of learning climate and work overload as competing organizational forces, with employee engagement serving as the mediating mechanism that explains how these conditions shape adaptive performance outcomes. Conclusions: The study concludes that organizations seeking to enhance adaptive performance among Generation Z workers should prioritize initiatives that foster engagement, such as creating supportive learning environments and managing workload demands effectively. Type of Paper: This paper is an empirical research paper.